PRINCIPAL LEADERSHIP STYLE AND ITS EFFECT ON TEACHERS PERFORMANCE - Elpisah, Elpisah; Hartini, Hartini (Universitas Brawijaya, Indonesia, 2019)
This study aims to analyze the effect of the application of leadership style on the teacher's performance and the dominant leadership style on the teacher's performance. The method used in this research is multiple regression analysis methods with SPSS. The object of this research is Junior high school in North Galesong District, Takalar District. This study used a sample of 47 people. The results showed that the leadership style had a positive and significant effect on the teacher's performance, and the dominant leadership style that influencedthe teacher's performance was delegative leadership style. This finding is an input for the principal to be able to understand the characteristics and enhance harmony with teachers for the achievement of educational goals.